2019
DOI: 10.1002/ece3.5577
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific distribution of oak rhizosphere‐associated oomycetes revealed by cytochrome c oxidase subunit II metabarcoding

Abstract: The phylum Oomycota comprises important tree pathogens like Phytophthora quercina, involved in central European oak decline, and Phytophthora cinnamomi shown to affect holm oaks among many other hosts. Despite the importance to study the distribution, dispersal and niche partitioning of this phylum, metabarcoding surveys, and studies considering environmental factors that could explain oomycete community patterns are still rare. We investigated oomycetes in the rhizosphere of evergreen oaks in a Spanish oak wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 98 publications
2
15
0
Order By: Relevance
“…A study conducted only on peat bogs, using ad hoc primers, revealed nevertheless the occurrence of 34 phylotypes, most of which could not be assigned to known species (Singer et al 2016). Few plant-associated oomycetes were found in the roots of oaks (Sapp et al 2019), in that of Arabidopsis thaliana (Sapp et al 2018) and in various other plant roots along a glacier chronosequence (Dickie et al 2019). Their complex life cycle, including a stage with large, mycelium-like structures protected by cell walls, the occurrence of motile cells for dispersion and thick-walled resting stages (Beakes and Thines 2016), may explain their adaptability and dispersal potential.…”
Section: Introductionmentioning
confidence: 98%
“…A study conducted only on peat bogs, using ad hoc primers, revealed nevertheless the occurrence of 34 phylotypes, most of which could not be assigned to known species (Singer et al 2016). Few plant-associated oomycetes were found in the roots of oaks (Sapp et al 2019), in that of Arabidopsis thaliana (Sapp et al 2018) and in various other plant roots along a glacier chronosequence (Dickie et al 2019). Their complex life cycle, including a stage with large, mycelium-like structures protected by cell walls, the occurrence of motile cells for dispersion and thick-walled resting stages (Beakes and Thines 2016), may explain their adaptability and dispersal potential.…”
Section: Introductionmentioning
confidence: 98%
“…For oomycetes, the metabarcoding of a region of the mitochondrial cytochrome oxidase (cox-) subunit 2 was done 53 . In the first PCR, primers attached to Illumina overhang adapter sequences were used (Nex_Cox2hud-F: 5′-TCGTCGGCAGCGTCAGATGTGTATAAGAGACAGGGCAAATGGGTTTTCAAGATCC-3′ and Nex_cox2_233D8r: 5′-GTCTCGTGGGCTCGGAGATGTGTATAAGAGACAGGAATATTCATARS-TCCARTACC-3′).…”
Section: Methodsmentioning
confidence: 99%
“…The dehesa covers an area of 500 ha with an altitude ranging between 350 m and 500 m above sea level. The territory is ideal for a study on tree vitality, as besides healthy areas, there are areas with a few diseased trees and severely affected areas (Sapp et al, 2019).…”
Section: Study Areamentioning
confidence: 99%